A Brief Discussion of the Generation of Meaning in Literary Works: A Hermeneutic Examination. (2nd October 2017) - Liyuan, Zhu
Abstract : The sources of meanings of literary works can be reviewed from various angles, one of which should be hermeneutics. Since the mid-20 th century, Western hermeneutics developed two important types of theories: one was the ontological hermeneutics from Martin Heidegger to Hans-Georg Gadamer, orientated towards the reader-centered theory in terms of the view of meanings; the other was the "hermeneutics as the general methodology of the Geisteswissenschaften" represented by Italian philosopher Emilio Betti, which affirmed that the author (subject) was one of the important sources of meanings of works. Due to intricate reasons, the latter exerted less influence, and Gadamer's ontological hermeneutics firmly stuck to a mainstay position in European and American academia. Since the 1990s, the circle of literature in China has also been greatly influenced by the hermeneutic theories from Heidegger and Gadamer to reception aesthetics, and Betti's impact almost can be neglected. Consequently, the view of meanings of literary works from the perspective of the reader-centered theory has been widely accepted, and the role of the author to endow initial meanings to his works was belittled and even denied. Since Zhang Jiang advanced the theory of "imposed interpretation" in 2014, academia has begun to reflect upon the one-sidedness of the reader-centered theory (relativism and subjectivism), and pick up the significance, which cannot be denied, of the author's meaning in the generation of meanings of literary works. In reference to Betti's hermeneutic train of thought and methodology, this essay, based on the practice of literary creation, concludes that the meaning of a literary work is created by the author and readers together in their interaction, and constantly generated in the dynamic process of the three factors of author, literary texts and readers, rather than by the author alone, or by readers solely.